Research on the Optimization of Basketball Teaching Content of Physical Education Major in Artificial Intelligence Colleges and Universities - Rongtong Qiao; Jie Ren; Yuguang Ji (Applied Bionics and Biomechanics)
The article uses the literature material law, expert interview method, mathematical statistics, the author of Suzhou University, Chengdu research, education of Guangdong Institute of Education, Guangdong teachers college education schools such as the current sports education professional study, and the similarities and differences in teaching outline of education of Guangdong province basketball specialty to conduct a comprehensive study and analysis and comparison on the current situation of education of Guangdong teachers college basketball in the system. This paper expounds the Guangdong education normal study and the Guangdong education status of school physical education professional basketball specialty courses, for Guangdong teachers college education reform of physical education professional basketball specializing in research, and the Guangdong education for theory reference.